The Novelties of the Law of Ukraine “On Limited Liability and Additional Liability Companies” (Law and Safety, 2019)
One of the most common types of legal entities are companies, in particular, Limited Liability Companies, that allow to combine material and other resources of several participants and at the same time reduce the risk of entrepreneurial activity for each of them.The article deals with the issue of the novelties in the legal regulation of the creation and activity of limited liability companies after the Law of Ukraine "On Limited Liability and Additional Liability Companies" act came into force. The adoption of this legislative act provides necessitates the analysis at the doctrinal level of a number of its rules, which regulate the activity of LLC in a new way.It is noted that for a long time the legal regulation of the activity of this type of companies remained limited and outdated, which led to the emergence of corporate conflicts. It is concluded that the process of streamlining corporate legislation is steadily ongoing, and the contradictions in the legislative regulation of corporate relations are gradually being eliminated.Regarding the novelties of regulation of the activity of limited liability companies, the author emphasizes the following positive aspects of the Law of Ukraine “On Limited Liability and Additional Liability Companies”: the number of participants in the LLC was lifted; the concept of "corporate agreement" is fixed; the only reason for the establishment of the LLC is the decision of its founders; minimize the list of information that must be displayed in the charter of LLC; included in the Law of the provisions of Chapter V “Substantial and Interest-Related party transactions”; a special chapter was introduced, which regulates the issues of creation and termination of the LLC (Chapter VI “Separation and Termination of the Company”); provides for the appearance of a local act on the regulation of corporate relations in the LLC - the agreement on the termination of the company; the procedure for setting up one or more new partnerships by transferring to it (them) a part of the assets, liabilities and liabilities of an existing limited liability company is regulated in detail.
Keywords: legal regulation; limited liability company; corporate agreement; significant transactions; corporate law